Lécba pacientů s relabovaným/refraktérním Hodgkinovým lymfomem - Mociková, H; Pytlík, R; Raida, L; Sýkorová, A; Marková, J; Král, Z; Jindra, P; Steinerová, K; Válková, V; Trnková, M; Vacková, B; Trnený, M; et al. (Klinicka onkologie, 2011)
BACKGROUNDS: This retrospective study evaluated treatment outcomes in patients undergoing autologous stem cell transplantation (ASCT) for relapsed/refractory Hodgkin lymphoma (HL). PATIENTS AND METHODS: Overall, 194 HL patients treated with ASCT between 2000 and 2009 were analyzed. Survival was calculated using Kaplan-Meier method and differences in survival between subgroups with log-rank test. RESULTS: Best responses observed after ASCT: 124 complete and 35 partial remissions, 2 patients with stable disease and 33 relapses/progressions. During a median follow-up of 44 months, seventy patients after ASCT progressed/relapsed. Thirty-seven patients received salvage chemotherapy only with or without radiotherapy, 25 underwent allogeneic stem cell transplantation (SCT), 4 the second ASCT and 4 refused treatment. 5-year overall survival after ASCT was 71% and progression-free survival 54%. Median survival of the 70 patients relapsing after ASCT was 16.9 months. Median survival in patients after allogeneic SCT was 31.8 months and 12.4 months in patients treated with other modalities (p = 0.21). Overall mortality was 26.3% (51/194 patients): 13.4% progressions/relapses of HL and 12.9% non-relapse mortality. CONCLUSION: Efficacy of ASCT was confirmed in 54% progression-free survivors. Median survival after ASCT failure is relatively short. There is a slightly longer overall survival after allogeneic SCT, although not statistically significant when compared to other approaches.
Keywords: Young Adult; Recurrence; Male; Survival Rate; progrese nemoci; mladý dospělý; Adolescent; Adult; dospělí; mužské pohlaví; Disease Progression; recidiva; transplantace kmenových buněk; mladiství; autologní transplantace; Hodgkin Disease; lidé; ženské pohlaví; Stem Cell Transplantation; Humans; Hodgkinova nemoc; Transplantation, Autologous; Female; lidé středního věku; indukce remise; míra přežití; Middle Aged; Remission Induction